Chapter Unicum glaciei. Le geografie estreme di Croce del Sud - Salvadori, Diego (Biblioteca di Studi di Filologia Moderna, 2021)
This essay offers a geocritical reading of Croce del Sud (2020), in the attempt to trace connections with other areas of Claudio Magris' macro-text and, above all, to highlight the extreme evolution of his literary geography, here resolved in an empty, glacial, absolute space, but at the same time open to the mythopoeic tension of other spaces: from Atlantis to Lemuria, from Thule to Antichthon.